Beitrag zur Klassifikation der mitteleuropäischen Olethreutinae (Lepidoptera: Tortricidae). - Obraztsov, Nicholas Sergeevitsch (Contributions to Entomology = Beiträge zur Entomologie, 1960)
The paper deals with descriptions of seven new genera of the Olethreutinae, established by the author for some Central European species, and nomenclature notes on those and some other species.Nomenclatural Actsherrichiana Obraztsov, 1960 (Barbara), spec. n.mughiana (Zeller, 1868) (Blastesthia), comb. n. hitherto Retinia turionella mughiana Zeller, 1868posticana (Zetterstedt, 1840) (Blastesthia), comb. n. hitherto Coccyx posticana Zetterstedt, 1840turionella (Linnaeus, 1758) (Blastesthia), comb. n. hitherto Phalaena Tinea turionella Linnaeus, 1758boisduvaliana (Duponchel, 1836) (Capricornia), comb. n. hitherto Carpocapsa boisduvaliana Duponchel, 1836cespitanus (Hübner, 1822) (Celyphoides), comb. n. hitherto Olethreutes cespitana Hübner, 1822flavipalpanus (Herrich-Schäffer, 1848) (Celyphoides), comb. n. hitherto Tortrix flavipalpana Herrich-Schäffer, 1848textana (Frölich, 1828) (Froelichia), comb. n. hitherto Tortrix textana frölich, 1828margarotana (Heinemann, 1863) (Gravitarmana), comb. n. hitherto Retinia margarotana Heinemann, 1863rivulana (Scopoli, 1763) (Paracelypha), comb. n. hitherto Phalaena rivulana Scopoli, 1763penthinana (Guenée, 1845) (Pristerognatha), comb. n. hitherto Sericoris penthinana Guenée, 1845clausthaliana (Saxesen, 1840) (Pseudohermenias), comb. n. hitherto Phalaena clausthaliana Saxesen, 1840Blastesthia Obraztsov, 1960 (Tortricidae), gen. n.Capricornia Obraztsov, 1960 (Tortricidae), gen. n.Celyphoides Obraztsov, 1960 (Tortricidae), gen. n.Froelichia Obraztsov, 1960 (Tortricidae), gen. n.Paracelypha Obraztsov, 1960 (Tortricidae), gen. n.Pristerognatha Obraztsov, 1960 (Tortricidae), gen. n.Pseudohermenias Obraztsov, 1960 (Tortricidae), gen. n.